Evolution of Meniscal Biomechanical Properties with Growth: An Experimental and Numerical Study - Marco Ferroni; Beatrice Belgio; Giuseppe M. Peretti; Alessia Di Giancamillo; Federica Boschetti (Bioengineering, 2021)
The menisci of the knee are complex fibro-cartilaginous tissues that play important roles in load bearing, shock absorption, joint lubrication, and stabilization. The objective of this study was to evaluate the interaction between the different meniscal tissue components (i.e., the solid matrix constituents and the fluid phase) and the mechanical response according to the developmental stage of the tissue. Menisci derived from partially and fully developed pigs were analyzed. We carried out biochemical analyses to quantify glycosaminoglycan (GAG) and DNA content according to the developmental stage. These values were related to tissue mechanical properties that were measured in vitro by performing compression and tension tests on meniscal specimens. Both compression and tension protocols consisted of multi-ramp stress–relaxation tests comprised of increasing strains followed by stress–relaxation to equilibrium. To better understand the mechanical response to different directions of mechanical stimulus and to relate it to the tissue structural composition and development, we performed numerical simulations that implemented different constitutive models (poro-elasticity, viscoelasticity, transversal isotropy, or combinations of the above) using the commercial software COMSOL Multiphysics. The numerical models also allowed us to determine several mechanical parameters that cannot be directly measured by experimental tests. The results of our investigation showed that the meniscus is a non-linear, anisotropic, non-homogeneous material: mechanical parameters increase with strain, depend on the direction of load, and vary among regions (anterior, central, and posterior). Preliminary numerical results showed the predominant role of the different tissue components depending on the mechanical stimulus. The outcomes of biochemical analyses related to mechanical properties confirmed the findings of the numerical models, suggesting a specific response of meniscal cells to the regional mechanical stimuli in the knee joint. During maturation, the increase in compressive moduli could be explained by cell differentiation from fibroblasts to metabolically active chondrocytes, as indicated by the found increase in GAG/DNA ratio. The changes of tensile mechanical response during development could be related to collagen II accumulation during growth. This study provides new information on the changes of tissue structural components during maturation and the relationship between tissue composition and mechanical response.